Citric acid incorporated in a chitosan film as an active packaging material to improve the quality and duration of matured cheese shelf life - Ressutte, Jéssica Barrionuevo; Saranti, Tascila Ferreira Da Silva [UNESP]; Moura, Márcia Regina de [UNESP]; Pozza, Magali Soares dos Santos; Scapim, Mônica Regina da Silva; Stafussa, Ana Paula; Madrona, Grasiele Scaramal (Cambridge University Press (CUP), 2022)
Chitosan-based film incorporated with citric acid was prepared by the casting method for application in a Brazilian matured cheese. Three formulations of cheese were processed, with the intention of evaluating the application of a starter culture and the effect of the film in terms of its physiochemical, microbiological, and sensorial characteristics. It was observed by scanning electron microscopy (sem) analysis that the film has a homogeneous appearance, and the crosslinking between citric acid and chitosan was confirmed by the Fourier transform infrared spectroscopy (FTIR) analysis. The cheese with chitosan-based film presented lower weight loss (5.2%) and showed antimicrobial activity against aerobic mesophilic bacteria. All samples showed high rates of sensorial acceptability (>79%), with no significant differences between them. It is apparent that the chitosan film maintained the typical cheese characteristics. Therefore, chitosan and citric acid film can be used to improve the characteristics of matured cheese and extend its shelf life.
Keywords: Active packaging; cheese; food packaging; lactic culture; shelf life